The horn handbook - Reynolds, Verne 1926- (Amadeus Press, 1997)
This immensely practical handbook is designed to provide both the student and teacher of the horn the tools needed to achieve excellence in all areas of horn playing. The work of a musician, composer, and teacher at Rochester, New York's Eastman School of Music, it is the first book to cover the topic, presenting a broad introduction to horn study, practice, and performance. The book confronts the problems faced by horn players from their early instruction to the beginning of their professional careers. The author emphasizes the development of a broad musicianship through ear-training, score study, and the investigation of music beyond the horn literature. Leading the player and teacher through the etude, solo, chamber music, and orchestral literature of the horn, the book also provides examples of exercises for warm-up and for perfecting technique.
Keywords: Hoorns (muziek); Uitvoeringspraktijk; Horn (Musical instrument) -- Instruction and study; Hornspiel